A taxonomic review of the genus Amicta Heylaerts, 1881 in North Africa, Near and Middle East (Lepidoptera, Psychidae, Oiketicinae, Acanthopsychini) - Arnscheid, Wilfried R.; Rajaei, Hossein; Sobczyk, Thomas (Zootaxa, 2021)
The genus Amicta Heylaerts, 1881 is revised on the basis of morphological and molecular studies. It is shown that, in addition to the already known taxa, there are three others that had previously remained unknown and are therefore described here as Amicta lutensis sp. nov., Amicta bouhedmaensis sp. nov. and Amicta chambiana sp. nov. Furthermore, the status of three more taxa is discussed and all three are raised to species rank: Amicta nigrescens Staudinger, 1900 stat. rev., Amicta acutella Krüger, 1931 stat. rev. and Amicta arabica (Wiltshire, 1949) stat. rev. It has also been shown that the genus Hyalopteronia Solyanikov, 2002 syn. nov. is synonymous with Amicta Heylaerts, 1881. The type species Hyalopteronia davarica Solyanikov, 2002 is recombined and placed with Amicta: Amicta davarica (Solyanikov, 2002) comb. nov., and Amicta syrtana Krüger, 1939 syn. nov. regarded as junior synonym of A. murina Krüger 1939. The results of this study give an overview of the systematics and distribution of the genus Amicta (with the exception of the species from the Canary Islands).